Economic Spacing and Rotation Decisions in Farm Forestry - Rawat, J. K. (Indian Forester, 1990)
A model for a eucalypts farm managed by a profit maximizing owner bas been developed. One seedling crop followed by one coppice crop of Eucalyptus bybrid have been taken into account. Subject to the cost of planting, diameter distribution of crop at varioos ages and densities, market price of the output (timber and firewood) and discount rates, the most economic combination of spacing (i.e., planting denesily) and rotation age have been determined. Sensitivity of these results to planting costs and wood prices bave been examined. Usefulness of such analysis to the farmers in management of tree crops is highlighted. The results show that at discount rates between 12-15 per cent and a planting cost of over Rs. 1.00 per plant, the optimal rotation length is 9 years or longer. Optimal spacing works out to be wider than 2 Ã— 2 m. The rotation length, however, is not very sensitive to changes in wood prices or planting costs and a rational farmer largely responds by adjusting the amount of initial investment (i.e., initial density of planting).